Chaetomitrium Beccarii - Monica Suleiman; Hiroyuki Akiyama (Museum of Nature and Human Activities, 2014)
(1) Stems are long and creeping with regularly-pinnate and slightly flattened branches; (2) stem leaves are concave, strongly incurved at one side with strongly spinose-serrate and geminate margins; (3) lamina cells are strongly prorate and spiculose-prorate or spinose in upper half; (4) branch leaves are distinctly concave, with shortacuminate and constricted apices.